Examining the Influences of Word-of-Mouth towards Sequels in Motion Picture Industry and the Effects of Product Knowledge and Tie-strength on Word-of-Mouth Behaviour - Cheng, Chenxiao (2008)
Research purpose: This paper aims to investigate the influences of Word-of-Mouth communication and critics reviews, advertising, movie genres and previous series quality have on consumers level of satisfaction towards sequels in the motion picture industry in U.K. In addition, this article also attempts to examine the degree of influences that Word-of-Mouth exerts across different product knowledge levels and scale of social-ties.